REFORM OF MATERNAL AND CHILD HEALTH SERVICES DURING THE COVID-19 PANDEMIC: IS IT NECESSARY? - Wardani, Yuniar; Santri, Ichtiarini Nurullita (Universitas Ahmad Dahlan, 2021)
The COVID-19 pandemic has impacted the health crisis and led to significant government policy changes with the maternal and child health care system. Long-term termination of essential services affects the risk of losing trust in the health system, decreasing services use. Health service reform is carried out to maintain the sustainability of health services. Priority services aim to ensure access to sexual and reproductive health, growth monitoring, screening for acute malnutrition in children, mothers, and pregnant women. Furthermore, implement a health information system to support maternal and child health and a robust system to monitor and respond to real-time data during COVID-19.